The acidity dependence of the fluorescence of β-naphthylamin - Capomacchia, Anthony C. (1972)
The change of hybridization of β-naphthylamine from sp3 to sp2, subsequent to excitation is found to have little effect upon the entropy of protonation of β-naphthylamine in the lowest excited singlet state. Solvent relaxation of the neutral amine, subsequent to excitation and as a result of dipole-dipole interactions, is shown to play an important role in the energy of the lowest excited singlet state and the pKa∗ value. The rates of protonation and dissociation of excited β-naphthylamine appear to be slightly slower than the rate of fluorescence of the β-naphthylammonium ion.